Obtaining Status Descriptions via Automatic Analysis of Hospital Patient Records - Boytcheva, S.; Nikolova, I.; Paskaleva, E.; Angelova, G.; Tcharaktchiev, D.; Dimitrova, N. (Informatica)
Obtaining Status Descriptions via Automatic Analysis of Hospital Patient Records